2021
DOI: 10.1007/s40843-020-1628-6
|View full text |Cite
|
Sign up to set email alerts
|

Widely tunable optical properties via oxygen manipulation in an amorphous alloy

Abstract: The ability to widely tune the optical properties of amorphous alloys is highly desirable especially for their potential applications in optoelectronic devices. In this work, we demonstrate that introducing oxygen into an amorphous alloy system of Co-Fe-Ta-B enables the formation of various amorphous derivatives ranging from metals to semiconductors, and eventually to insulators. These oxygencontaining amorphous derivatives gradually become transparent with the opened bandgaps, leading to a continuous increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Previous works have shown that oxidation of Gd x Co 1− x results in a structural transformation from an amorphous alloy to amorphous oxide. 37,38 Here, XRD spectra (Fig. S9, ESI†) from GdCoO shows that the alloys are amorphous for all oxygen flow rates, which means the magnetic properties are a consequence of the exchange interactions in the absence of a long-range structural order.…”
Section: Resultsmentioning
confidence: 99%
“…Previous works have shown that oxidation of Gd x Co 1− x results in a structural transformation from an amorphous alloy to amorphous oxide. 37,38 Here, XRD spectra (Fig. S9, ESI†) from GdCoO shows that the alloys are amorphous for all oxygen flow rates, which means the magnetic properties are a consequence of the exchange interactions in the absence of a long-range structural order.…”
Section: Resultsmentioning
confidence: 99%